KRAS signaling in malignant pleural mesothelioma - Antonia Marazioti; Anthi C Krontira; Sabine J Behrend; Georgia A Giotopoulou; Giannoula Ntaliarda; Christophe Blanquart; Hasan Bayram; Marianthi Iliopoulou; Malamati Vreka; Lilith Trassl; Mario A A Pepe; Caroline M Hackl; et al. (EMBO Molecular Medicine, 2021)
Abstract Malignant pleural mesothelioma (MPM) arises from mesothelial cells lining the pleural cavity of asbestos‐exposed individuals and rapidly leads to death. MPM harbors loss‐of‐function mutations in BAP1, NF2, CDKN2A, and TP53, but isolated deletion of these genes alone in mice does not cause MPM and mouse models of the disease are sparse. Here, we show that a proportion of human MPM harbor point mutations, copy number alterations, and overexpression of KRAS with or without TP53 changes. These are likely pathogenic, since ectopic expression of mutant KRASG12D in the pleural mesothelium of conditional mice causes epithelioid MPM and cooperates with TP53 deletion to drive a more aggressive disease form with biphasic features and pleural effusions. Murine MPM cell lines derived from these tumors carry the initiating KRASG12D lesions, secondary Bap1 alterations, and human MPM‐like gene expression profiles. Moreover, they are transplantable and actionable by KRAS inhibition. Our results indicate that KRAS alterations alone or in accomplice with TP53 alterations likely play an important and underestimated role in a proportion of patients with MPM, which warrants further exploration.